Implementation of Decentralized Blockchain E-voting - Moin Khan, Saad; Arshad, Aansa; Mushtaq, Gazala; Khalique, Aqeel; Husein, Tarek (EAI Endorsed Transactions on Smart Cities, 2020)
E-voting reduced the cost of election and provided convenience to some extent as compared to the traditional approach of pen and paper but it was considered to be unreliable as anyone having access to the machine physically can obstruct the machine and alter the votes. Also in order to control the entire procedure from electronic voting to electoral results and tracking the outcomes, a central system is required. Voters are not completely secure as vote can be targeted easily. It also possesses a great threat to the right to vote and transparency. This paper provides a solution for removing inconveniences from conventional elections using blockchain that has emerged as an exciting technology for various application due to its unique characteristics that outperform other technologies. The goal of this research is to establish a system for e-voting that is decentralized rather than centralized by using blockchain technology that guarantees protection to electorate’s identity, data transfer privacy and verifiability by an open and transparent voting process.
Keywords: E-Voting; Blockchain; Smart Contracts; Ethereum Cryptocurrency